2021
DOI: 10.3390/chemosensors9110319
|View full text |Cite
|
Sign up to set email alerts
|

Colorimetric Sensing of Benzoyl Peroxide Based on the Emission Wavelength-Shift of CsPbBr3 Perovskite Nanocrystals

Abstract: Using the ionic salt characteristics of CsPbBr3 perovskite nanocrystals (CsPbBr3 NCs), the fluorescence wavelength of CsPbBr3−xIx NCs could be changed by the halogen exchange reaction between CsPbBr3 NCs and oleylammonium iodide (OLAM-I). Under the excitation of a 365 nm UV lamp and the increase of OLAM-I concentration, the content of iodine in CsPbBr3−xIx NCs increased, and the fluorescence emission wavelength showed a redshift from 511.6 nm to 593.4 nm, resulting in the fluorescence color change of CsPbBr3 N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…By virtue of this sensing mechanism, a fluorescent biosensor for BPO was successfully fabricated, and the developed biosensor achieved a linear range of 0−240 μmol L −1 with a low LOD of 0.13 μmol L −1 , which has also obtained good recoveries ranging of 94.0−112.0% in flour. 100 4.2. Fruit and Vegetable Products.…”
Section: Cereal Productsmentioning
confidence: 99%
See 1 more Smart Citation
“…By virtue of this sensing mechanism, a fluorescent biosensor for BPO was successfully fabricated, and the developed biosensor achieved a linear range of 0−240 μmol L −1 with a low LOD of 0.13 μmol L −1 , which has also obtained good recoveries ranging of 94.0−112.0% in flour. 100 4.2. Fruit and Vegetable Products.…”
Section: Cereal Productsmentioning
confidence: 99%
“…Benzoyl peroxide (BPO), a typical illegal additive in flour products, can oxidize natural pigments to make flour whiter and combine with proteins to form a cross-linked structure for increasing their strength and stability, while the residues of BPO in cereal products can damage the liver and other organs of human bodies. , To rapidly detect of BPO in flour, Zhang et al reported CsPbBr 3 perovskite nanocrystals with narrow half-peak width, high quantum yield, and halogen atom exchange as luminogens, and their fluorescent wavelength could be shifted by interaction with I – owing to the formation of CsPbBr 3– x I x nanocrystals, while this process could be inhibited by BPO due to their oxidized activity of I – . By virtue of this sensing mechanism, a fluorescent biosensor for BPO was successfully fabricated, and the developed biosensor achieved a linear range of 0–240 μmol L –1 with a low LOD of 0.13 μmol L –1 , which has also obtained good recoveries ranging of 94.0–112.0% in flour …”
Section: Applications In Food Productsmentioning
confidence: 99%
“…When BPO was added to the above solution, the original PL emission was blueshifted within 1–2 min. Zhang and co-workers also used luminescent CsPbBr 3 NCs (synthesized with the hot-injection method; PLQY = 87%) to detect BPO [ 119 ]. The linear range of BPO detection was observed between 0 µM and 120 µM, with an LOD of 0.13 µM.…”
Section: Cspbx 3 (X = CL Br and I) And Composites ...mentioning
confidence: 99%
“…The detection/quantification of specialized chemicals, such as CH 3 I, CH 2 Cl 2 , CH 2 Br 2 , benzoyl peroxide, and excessive acid number (AN), via anion exchange mechanisms [ 114 , 115 , 116 , 117 , 118 , 119 , 120 , 121 ] cannot be regarded as a specific quantification procedure because of its similarity to anion detection. This should be critically investigated to pursue the “state-of-the-art” sensing procedure.…”
Section: Cspbx 3 (X = CL Br and I) And Composites ...mentioning
confidence: 99%
“…Recently, several colorimetric sensing studies have been reported using the wavelength-shift of the halogen exchange characteristics of C S PbX 3 NCs, in which the concentrations of Cl − and methylamine (MA) gas, as well as the peroxide number of edible oil, have been detected [ 18 , 29 , 30 , 31 ]. In addition, based on the similar consideration, colorimetric sensing approaches have been developed for the determination of chlorine, iodine and other trace elements in tap water [ 32 ], H 2 S in rat brain microdialysate [ 27 ] and benzoyl peroxide in flour and noodle samples [ 33 ].…”
Section: Introductionmentioning
confidence: 99%